Can homegardens assist in enhancing the domestic food security?’ A study in Jaffna Peninsula, Sri Lanka - Lowe, W.A.M.; Sinniah, J.; Jeyavanan, K.; Silva, G.L.L.P.; Pushpakumara, D.K.N.G. (Springer, 2021)
Due to the combination of trees, crops livestock and poultry, homegardens are well-known in providing socioeconomic and agro-ecological ser vices. This study was conducted to assess the potential contribution of homegardens toward securing domes tic food requirement. A questionnaire survey with ground trothing was conducted with 145 households in Jaffna peninsula. Socioeconomic data, floristic and fauna diversity and food consumption data were gathered. Average size of a family and homegarden was 4 members and 0.083 ha, respectively. Sixty-nine plant species were recorded including 10 vegetables, 18 fruit and 43 woody plant species. Approximately 50% of the homegardeners reared livestock and poultry. Food consumption of the households evalu ated based on the Food Consumption Score (FCS) of the World Food Program indicated that, 1, 12 and 73% households fell into poor, borderline and accept able FCS categories, respectively. Expenditure on food and beverages showed a positive relationship with FCS, explaining the dependency of households on market for food necessity. Coconut was the most common income commodity and the most dominant tree species in homegardens, according to Summed Dominance Ratio of tree species. It was revealed that animal proteins and pulses are truly important in securing domestic caloric availability. Except pulses, most of the crops in homegardens were falling into the least important category with respect to FCS. It was found that a household is more secured in terms of caloric availability when homegardens are highly diverse in livestock and poultry and has access to more animal proteins. Growing animals and crops to get valuable components in homegardens will assure enhancement of food security in the future. Thus, homegarden could be a potential approach in assuring domestic food security in the area
Keywords: Homegarden; Homegarden; FCS; Livestock; Crops